Od premonstratensów do benedyktynów. Klasztor św. Wawrzyńca w Kościelnej Wsi pod Kaliszem do połowy XIII w. - Kucharski, Gerard (Nasza Przeszłość, 2000)
The work presents the foundation process and people involved in bringing and providing the Norbertines and then the Benedictine monks in Kościelna Wieś near Kalisz. History of the monastery of St. Lawrence in the 12th and 13th centuries is inextricably associated with two orders: the Premonstratensians and the Benedictine monks. The Norbertines, governed by the rule of St. Augustine reformed by Saint. Norbert of Xanten, emphasized strict observation of the rule and the subordination of branch monasteries to the mother monasteries. In turn, the Benedictines, who applied a rule based on the honor of God and man, as well as obedience, were engaged in liturgy, intellectual activity and physical work. The beginnings of the monastery of St. Wawrzyniec in Kościelna Wieś is not completely known, but there are differences in the assessment of researchers as to the time of its creation. Sporadic source information and discrepancies in historians' positions mean that the date of the monastery's foundation remains a matter of debate. Moreover, there is no unanimity as to the founder of the monastery. Researchers put forward various proposals, often based on different chronological assumptions. Although the existence of the Premonstratensians in Kościelna Wieś near Kalisz ended in the early 1290s, their activity brought benefits to the region, especially in the context of contacts and protection. The Benedictines, who were the provost of the Tyniec monastery, received subsequent property grants, although their activity was limited by their dependence on the Tyniec abbey and the general decline in the importance of the order in Poland in favor of others, such as the Cistercians and Premonstratensians.
Keywords: kościelna wieś

Piotr Włostowic czy Piotr Wszeborowic? O fundacji i fundatorze klasztoru norbertanek w Strzelnie - Hewner, Katarzyna (Nasza Przeszłość: Studia z dziejów Kościoła i kultury katolickiej w Polsce, 2000)
Piotr Włostowic or Piotr Wszeborowic? The foundation and the founder of the Norbertine nunnery in Strzelno
Keywords: strzelno

Przeorysze i podprzeorysze klasztoru norbertanek w Strzelnie od końca XII wieku do 1837 r - Kabaciński, Ryszard; Karczewski, Dariusz (Nasza Przeszłość: Studia z dziejów Kościoła i kultury katolickiej w Polsce, 2000)
Abbesses and their deputies in the Norbertine nunnery at Strzelno from the end of the 12th century to 1837
Keywords: strzelno

Studia nad trzynastowiecznymi dokumentami klasztoru Norbertanek w Strzelnie - Karczewski, Dariusz (Studia Źródłoznawcze, 2000)
Keywords: strzelno

Jeszcze jedna próba datowania fundacji klasztoru premonstratensek w Strzelnie - Labuda, Gérard (Nihil superfluum esse: Studia z dziejów średniowiecza ofiarowane Profesor Jadwidze Krzyżaniakowej, 2000)
Another attempt at dating the foundation of the Premonstratensian nunnery in Strzelno
Keywords: strzelno